COMPARATIVE ANALYSIS OF THE EFFECT OF MACROECONOMIC FACTORS TOWARD IDX COMPOSITE INDEX AND FTSE BURSA MALAYSIA INDEX - Rahmani, Annisa Gilang; Banani, Ade; Widiastuti, Ekaningtyas (Journal Economics & Business Atmajaya Indonesia, 2019)
This article is titled ?Comparative Analysis of The Effect of Macroeconomic Factors toward Idx Composite Index and FTSE Bursa Malaysia Index?. The aims of this study are to determine the influence of macroeconomic factors toward the Indonesia?s and Malaysia?s index, and to compare the performance of those two indices. The macroeconomic factors studied were inflation rates, exchange rates, Gross Domestic Product (GDP), and WTI crude oil prices on Indonesian and Malaysian stock indices. This study took the period from January 2012 until December 2017 as a sample. The Indonesian stock market is represented by IDX Composite Index, while Malaysia is FTSE Bursa Malaysia. This research used Multiple Regression Linear Model as analysis tool. The result shows that the inflation rate has no effect on IDX Composite Index and FTSE Bursa Malaysia. While the exchange rate and GDP have a significant positive influence on IDX Composite Index and FTSE Bursa Malaysia. Vice versa, the WTI crude oil price does not affect IDX Composite Index and FTSE Bursa Malaysia. Both of these stock indices significantly proved to be different. The implication of this study is that the results of this study can be used as a reference for investors in choosing which index is better, Bank Indonesia and Bank Negara Malaysia in determining monetary policies made for each country.